Historicizing Fashion: Clothing, Culture, and Chores - Pandey, Anjani Shankar (Advances in Social Sciences Research Journal, 2021)
The present paper is a study on the history of clothing in ancient India to historicize fashion in the Ancient Indian context. Relying primarily on textual sources of the period The Kāmasūtra of Vatsyayana ( 4-5th CE) and The Nātyaśāstra of Bharata (200 BCE-200CE), the paper seeks to examine the implications on patterns of dressing: clothing and accessorizing on different social categories based on gender, class, and caste being governed by the power relations operating within the social milieu of the texts. By looking at varied range of social and gendered categories the essence of clothing and dressing has been observed and commented upon. It has been primarily argued that dressing patterns reveal homogeneity in a particular group, who were part of a heterogeneous whole.